Experimental investigation on the flowability properties of cohesive carbonaceous powders. (4th May 2017) - Guiling, Xu; Xiaoping, Chen; Cai, Liang; Pan, Xu; Changsui, Zhao
ABSTRACT: The flowability properties of two carbonaceous powers (anthracite coal and petroleum coke), including angle of repose (AOR), Hausner ratio (HR) and powder compressibility (C), etc., were determined. The effects of particle size, external moisture content (MC) and power type on powder flowability properties were investigated. The results indicate that as the powder particle size increases, the AOR, HR and C decrease, respectively, and the powder flowability becomes better. As the powder external MC increases, the AOR, HR and C increase, respectively, and the powder flowability becomes worse. The anthracite coal has lower values of AOR, HR and C, and higher values of flow function (FF) than those values of petroleum coke. Therefore, anthracite coal has better flowability compared to petroleum coke. Meanwhile, there exists a good linear correlation between AOR and HR.